2021
DOI: 10.3390/cancers13040875
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Real-World Data in Understanding Prostate Cancer Risk and Improving Clinical Care: Examples from Swedish Registries

Abstract: Real-world data (RWD), that is, data from sources other than controlled clinical trials, play an increasingly important role in medical research. The development of quality clinical registers, increasing access to administrative data sources, growing computing power and data linkage capacities have contributed to greater availability of RWD. Evidence derived from RWD increases our understanding of prostate cancer (PCa) aetiology, natural history and effective management. While randomised controlled trials offe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 89 publications
0
8
0
Order By: Relevance
“…Indeed, RCTs constitute the highest level of evidence to inform guideline development for CRC screening, but evidence from screening practices and RCTs is considered mutually complementary. Not all research questions regarding CRC screening can be addressed through RCTs [ 16 ]. For example, researchers cannot intervene to identify disparities in access to CRC screening and identify the real gains in screening practice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, RCTs constitute the highest level of evidence to inform guideline development for CRC screening, but evidence from screening practices and RCTs is considered mutually complementary. Not all research questions regarding CRC screening can be addressed through RCTs [ 16 ]. For example, researchers cannot intervene to identify disparities in access to CRC screening and identify the real gains in screening practice.…”
Section: Discussionmentioning
confidence: 99%
“…addressed through RCTs [16]. For example, researchers cannot intervene to identify disparities in access to CRC screening and identify the real gains in screening practice.…”
Section: Plos Medicinementioning
confidence: 99%
“…Real-world data initiatives have also taken shape in the Scandinavian countries. For instance, in Sweden studies concerning ovarian and prostate cancers have demonstrated the value of harnessing real-world data from registries and health records to investigate and understand the longer-term outcomes of cancer treatments ( Eriksson et al, 2018 ; Beckmann et al, 2021 ). Nonetheless, it is interesting to note that despite the long history of Nordic countries with establishing cancer registries ( Pukkala et al, 2018 ), there seems to be no clear lead in real-world data initiatives compared to other countries mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…However, real-world studies to verify the results obtained in RCTs continue to remain little used, particularly in the setting of BCR PC. A recent 2021 review demonstrated the value of a high-quality national register, the National Prostate Cancer Register (NPCR) of Sweden, in generating high-quality evidence in different PC settings, such as etiology, treatment, and adverse events' management [79].…”
Section: Differences Between Real World and Clinical Trials In The Ma...mentioning
confidence: 99%